Sistema embebido de reconstrucción 3d de entornos con KINECT V.1 - Morillo Celi, Michelle Nathaly (2019)
In the last years, embedded systems have been involved in great technological advances, with the aim of facilitating the daily life of the user. The use of embedded systems goes from the braking system of a car, to the control of a smart house. Its features include that the systems operate independently. This qualification work is to create an embedded system, which allows the reconstruction of any environment in three dimensions, using the Kinect V. 1 device. Since its launch in the year 2009, where it was born as a peripheral for the Xbox 360 video game console from Microsoft, has allowed the user to take control of the movements of the characters, only with bodily movements. It resulted in the device becoming nowadays an artificial vision system used by researchers from around the world. The Kinect sensor is extremely important in the project, because through it you can get the point cloud for the required reconstruction. For this we will also require a revolving platform, to capture the 360°of the environment to rebuild. For the processing of the data will be used a software programmed in Python, where the mathematical processes involved in obtaining the three-dimensional reconstruction of the environment will be performed. Matlab will also be used for the development of a GUIDE that allows the control, visualization and analysis of the final points cloud obtained. The result is obtaining a 3D rebuilt environment, which is processed on an SBC. This environment can be manipulated thanks to the different filters that has the application developed in Matlab, such as: resolution filters, segmentation and distance. Finally, an analysis of the results will be carried out, where it will be shown that the main objective of the project has been achieved.